(untitled) (Società e diritti, 2022)
Abstract The legal protection of intangible cultural heritage is the result of a long and complex process that culminated in the 2003 UNESCO Convention on the protection of intangible culturale heritage, and is still in progress in many legal systems. To this path is not foreign the role and the cultural contribution of cultural anthropology and in particular of one of its most eminent exponents, Claude Lévi Strauss, who, over the years, has maintained a long and fruitful relationship with UNESCO.